Novel Orally Administered Recombinant Anti-TNF Alpha Fusion Protein for the Treatment of Ulcerative Colitis: Results From a Phase 2a Clinical Trial. Issue 2 (February 2021) - Almon, Einat; Shaaltiel, Yoseph; Sbeit, Wisam; Fich, Alex; Schwartz, Doron; Waterman, Mattitiahu; Szlaifer, Mali; Reuveni, Hadar; Amit-Cohen, Bat-chen; Alon, Sari; Chertkoff, Raul; Paz, Alona; et al.
Abstract : Background and Objective: OPRX-106 is an orally administered BY2 plant cell-expressing recombinant TNF fusion protein (TNFR). Oral administration of OPRX-106 was shown to be safe and effective in inducing favorable anti-inflammatory immune modulation in humans. The current study was aimed at determining the safety and efficacy of OPRX-106 in patients with ulcerative colitis (UC). Methods: Twenty-five patients with active mild-to-moderate UC were enrolled in an open-label trial. Patients were randomized to receive 2 or 8 mg of OPRX-106 administered orally once daily, for 8 weeks. Patients were monitored for safety and efficacy including clinical response or clinical remission, based on the Mayo score. The histopathological improvement in Geboes score, calprotectin level and hs-CRP, and exploratory immune parameters by means of fluorescence-activated cell sorting and cytokine levels were monitored. Results: Oral administration of OPRX-106 was found to be safe and well tolerated without absorption into the circulation. Out of 24 patients, 18 completed the trial. The analysis of the patients completing treatment demonstrated clinical efficacy as measured by clinical response or remission in 67% and 28%, respectively. Reduction in calprotectin levels and improved Geboes score were noted in the majority of the treated patients. The beneficial clinical effect was associated with an increase in a CD4+CD25+FoxP3 subset of suppressor lymphocytes and a reduction in interleukin 6 and interferon gamma serum levels. Conclusions: Oral administration of the nonabsorbable OPRX-106 is safe and effective in mild-to-moderate UC, and not associated with immune suppression, while inducing favorable anti-inflammatory immune modulation.